Odonata (Insecta) diversity of Chinnar Wildlife Sanctuary, the southern Western Ghats, India - C.K. Adarsh (Journal of Threatened Taxa, 2015)
A study was conducted at Chinnar Wildlife Sanctuary, Idukki District, Kerala, the southern Western Ghats, to assess the diversity of odonates. We report 48 species of odonates, which include 31 species of Anisoptera (dragonflies) and 17 species of Zygoptera (damselflies). Among the dragonflies, the family Libellulidae dominated with 25 species, while Coenagrionidae with seven species was the dominant family among the damselflies. The odonate diversity of Chinnar WS accounted for 31.16 % of the odonates in Kerala and 27.58% of the odonates of the Western Ghats. Chinnar also recorded two species of odonates that are endemic to the Western Ghats, which are, the Pied Reed Tail Protosticta gravelyi and the Travancore Bamboo Tail Esme mudiensis.